Diagnosis and management of retinal venous and arterial occlusive disease - Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Przewodnik Lekarza/Guide for GPs, 2010)
Retinal venous and arterial occlusive disease leads to a sudden painless visual loss including no light perception in some cases. It is an emerging state requiring prompt ophthalmic as well as systemic diagnosis because ocular symptoms may herald the onset of life-threatening disorders. In spite of many clinical trials there is no consensus on a standardized treatment regimen for retinal vessels occlusive disorders. There is clinical evidence that in majority of cases the efficacy of current therapeutic strategies for an acute phase of retinal vessels occlusive disorders is doubtful. Thus it is very important to prevent the development of local complications and to diagnose and treat of any disorder that is potentially a risk factor for retinal vessels occlusive disorder. The aim of this review is to provide an update on the progress of diagnosis and current therapies for retinal vessels occlusive disorders and to point out the role of general medicine specialist in management of these patients.